Temporal constraints on future accumulation-area loss of a major Arctic ice cap due to climate change (Vestfonna, Svalbard) - Möller, Marco; Schneider, Christoph (Scientific Reports, 2015)
Die Zweitveröffentlichung der Publikation wurde durch Studierende des Projektseminars "Open Access Publizieren an der HU" im Sommersemester 2017 betreut. Nachgenutzt gemäß den CC-Bestimmungen des Lizenzgebers bzw. einer im Dokument selbst enthaltenen CC-Lizenz. Arctic glaciers and ice caps are major contributors to past, present and future sea-level fluctuations. Continued global warming may eventually lead to the equilibrium line altitudes of these ice masses rising above their highest points, triggering unstoppable downwasting. This may feed future sea-level rise considerably. We here present projections for the timing of equilibrium-line loss at the major Arctic ice cap Vestfonna, Svalbard. The projections are based on spatially distributed climatic mass balance modelling driven by the outputs of multiple climate models from the Coupled Model Intercomparison Project Phase 5 (CMIP5) forced by the Representative Concentration Pathways (RCPs) 2.6, 4.5, 6.0 and 8.5. Results indicate strongly decreasing climatic mass balances over the 21st century for all RCPs considered. Glacier-wide mass-balance rates will drop down to −4 m a−1 w.e. (water equivalent) at a maximum. The date at which the equilibrium line rises above the summit of Vestfonna (630 m above sea level) is calculated to range between 2040 and 2150, depending on scenario. Peer Reviewed